2013
DOI: 10.1186/1471-2377-13-86
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, characteristics and correlates of a positive-dementia screen in patients on antiretroviral therapy in Bamenda, Cameroon: a cross-sectional study

Abstract: BackgroundIn this study we assess the prevalence, characteristics as well as socio-demographic and clinical correlates of a positive screen for HIV-associated dementia in a group of patients on antiretroviral therapy (ART) in Bamenda, Cameroon.MethodsIn a cross-sectional study, a structured questionnaire was used to collect data on 400 patients attending the Bamenda Regional Hospital AIDS-treatment Centre. Patients were assessed for neurocognitive function using the International HIV Dementia Scale (IHDS) to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(66 citation statements)
references
References 24 publications
1
57
7
Order By: Relevance
“…The HAD prevalence indicated by the IHDS in the current study was higher than the prevalence of 11% identified by psychiatrist’s interview in Vietnam [31] but was similar to prevalences reported in previous studies using the IHDS in the United States of America (37.9%), Canada (39.4%), and India (32.5%) [45, 48, 49], although lower than most studies in Africa, where reported HAD prevalence has ranged from 54.4 to 85% [50, 51]. Since these studies also employed the IHDS the difference in HAD prevalence might be due to HIV severity, especially at ART initiation [50]. Our findings indicate an urgent need for screening for SOMD and provision of appropriate support and treatment for HIV positive outpatients in Vietnam.…”
Section: Discussionsupporting
confidence: 84%
“…The HAD prevalence indicated by the IHDS in the current study was higher than the prevalence of 11% identified by psychiatrist’s interview in Vietnam [31] but was similar to prevalences reported in previous studies using the IHDS in the United States of America (37.9%), Canada (39.4%), and India (32.5%) [45, 48, 49], although lower than most studies in Africa, where reported HAD prevalence has ranged from 54.4 to 85% [50, 51]. Since these studies also employed the IHDS the difference in HAD prevalence might be due to HIV severity, especially at ART initiation [50]. Our findings indicate an urgent need for screening for SOMD and provision of appropriate support and treatment for HIV positive outpatients in Vietnam.…”
Section: Discussionsupporting
confidence: 84%
“…As compared to prior studies, the current finding is similar with the result of a study conducted in India (32.5%) (18), a study done in Nigeria (34.4%) [28] and an earlier Metaanalysis (systemic review) in Sub-Saharan area (30.9%) (2). However, it is less than the findings of previous studies undertaken in Botswana (38%) (21), a study in the international community (37%) (15), a study done in Cameroon (85%) [29], a study conducted in Asia (90%) (19) and a Ugandan study (46.49%) (30,31,32). …”
Section: Discussionmentioning
confidence: 80%
“…21,22 The high prevalence found in African countries could potentially be due to more advanced HIV infection among study participants where only PLWHA with CD4 counts less than 200 or HIV stage 4 were on ART. 18,20 In the current study, the mean CD4 count was approximately 400 and most of the participants (92%) were in HIV stage 1. Alternatively, the high prevalence might also be due to the psychometric properties of the IHDS in different settings such as South Africa where sensitivity and specificity were 45% and 79% at the cutoff at 10.…”
Section: Discussionmentioning
confidence: 55%
“…With estimated prevalence of 50%, type I error rate of a ¼ 5% and estimation error of 5%, at least 385 participants were required. Since the reported prevalence of probable HAD ranged from 21.1% to 85%, [17][18][19][20][21][22] the sample size was sufficiently large to estimate the prevalence of HAD.…”
Section: Setting and Participantsmentioning
confidence: 99%